The 'Taman Telaga Teratai' Batik Motif as a Traditional Aesthetic Visual Communication Media in the Cirebon Palace: Levi-Strauss Approach - Komarudin Kudiya (Mediator: Jurnal Komunikasi, 2023)
The aim of this research is to obtain a relationship between the aesthetic visual communication media and the functional relationship between phenomena that is more accurate and definite from the traditional batik motif of Taman Telaga Teratai in the Cirebon Palace. The fact is that the Cirebon Keraton batik and its decorative styles have distinctive differences in the three palaces and one unique Peguron. The diversity of these ornamental styles is characteristic and unique within the Kasepuhan Palace, Kanoman Palace, Kacirebonan Palace, and Peguron Kaprabonan. The method used is a qualitative approach, combined with an analytical descriptive method in the form of observations and interviews with cultural stakeholders of the Cirebon palace. This research resulted in the finding that Cirebon batik artisans have the courage and flexibility in realizing self-expression and the consistency of producing traditional batik by giving symbolic meaning, as well as adding to the depth of philosophical meaning in the Cirebon royal batik genre. The conclusion of this study is that attractive and patterned aesthetic visual communication in the Cirebon traditional batik artisan community can contribute to the emergence of new traditional batik motifs with the Cirebon palace batik genre which contain symbolic and philosophical values ​​of the Cirebon Palace cultural tradition.